2023
DOI: 10.1002/anie.202309295
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Directed Site‐Selective Csp3‐H Borylation of Saturated Cyclic Amines

Abstract: The borylation of Csp3‐H bonds is a challenging transformation that is typically restricted to transition metal catalysis. Herein, we report the site‐selective metal‐free Csp3–H borylation of saturated cyclic amines. It is possible to selectively borylate piperidine derivatives at the α or β positions according to the reaction conditions. The mechanism was supported by NMR spectroscopy, calorimetry experiments and density functional theory (DFT) computations. It suggests that the piperidine is dehydrogenated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Very recently, Fontaine's group first disclosed an elegant strategy for the metal-free Csp 3 –H borylation of 2-dialkylaminopyridines using BBr 3 (Scheme 23). 69 Mechanism studies found that an enamine is formed in the borylation followed by subsequent Csp 3 –H insertion or electrophilic borylation.…”
Section: C–h Bond Borylationmentioning
confidence: 99%
“…Very recently, Fontaine's group first disclosed an elegant strategy for the metal-free Csp 3 –H borylation of 2-dialkylaminopyridines using BBr 3 (Scheme 23). 69 Mechanism studies found that an enamine is formed in the borylation followed by subsequent Csp 3 –H insertion or electrophilic borylation.…”
Section: C–h Bond Borylationmentioning
confidence: 99%
“…1B ). 7 More recently, we showed that the chemistry is not limited to only hydroxyl and Bpin, but it can also be used for installing halogens to phenyl pyridines and aryl aldehydes ( Fig. 1B ).…”
Section: Introductionmentioning
confidence: 97%